Association between blood glucose levels at admission and severity of COVID-19 patients - Asysyifa, Nurul; Sari, Shinta Dewi Permata; Martalena, Dewi (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2023)
Hyperglycemia can be experienced by corona virus disease (COVID-19) patients due to the invasion of severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) into pancreatic cells or other mechanisms such as insulin resistance, counter-regulatory, stress induction, and glucocorticoid therapy. Hyperglycemia can stimulate the production of reactive oxygen species (ROS) and pro-inflammatory cytokines leading to an increase in the disease severity.  Based on the clinical and laboratory criteria, the severity of COVID-19 patients is classified into asymptomatic, mild, moderate, severe, and critical. This study aimed to investigate the association between blood glucose levels at admission and the severity of COVID-19 patients with and without diabetes mellitus (DM). It was a cross-sectional study using secondary data from COVID-19 patients in Pondok Kopi Jakarta Islamic Hospital from April to June 2021. This study involved 340 patients with comorbid DM (n=78) and without comorbid DM (n=262). The Mann-Whitney and Spearman correlation test were used. A significant difference between random blood glucose levels in comorbid DM patients and patients without comorbid DM (p<0.05). However, there is a weak correlation between random blood glucose levels and severity with comorbid DM (r=0.112) and without comorbid DM (r=0.129). In conclusion, a positive and weak correlation between blood glucose levels at admission and the severity of COVID-19. The severity increases as the blood sugar level increases. Further study needs to be performed considering other comorbid conditions.